The Impact of Operating Lease Practices on the Financial Performance of Nigerian Conglomerates - Hameed, Raimi Adoke; Waziri , Abba Umar (Minhaj International Journal of Economics and Organization Sciences, 2025)
The financial performance of conglomerate firms in Nigeria has raised significant concerns among stakeholders. There may be several factors that impede such performance. The purpose of this study is to investigate how operating leases and the financial performance of five conglomerate companies listed on the Nigerian Exchange Group as of December 31, 2024, relate to one another. The timeframe encompassed in this study spans a decade, specifically from 2015 to 2024. Financial performance was measured by dividing profit after taxes by total assets. The following metrics are used to measure operating leasing: assets tangibility, are measured by dividing fixed assets by total assets, lease income, net sales to fixed assets, and total lease to total revenue. The ex-post facto research design was employed in this investigation. The following results were achieved during the data analysis process based on descriptive statistics, Hausman test analysis, random effect, fixed effect, and regression analysis. Following hypotheses testing, it was discovered that lease income and financial success were strongly correlated. In the meantime, there is a negative correlation between financial success and other variables, such as overall assets and asset tangibility. In order to guarantee higher profits, the report advises managers of big multinational companies to make efficient use of the company's resources by allocating shareholder funds to lucrative endeavors.